High Priority Arbitration for Less Burst Data Transactions for Improved Average Waiting Time of Multi-Processor Cores - Noami, Ahmed; Kumar, Boya Pradeep; Paidimarry, Chandra Sekhar; Alahdal, Abdullah; Safi, Nada (Applied Science and Engineering Progress, 2021)
The multi-processor cores in SoC which have high burst data transactions can play a critical role while accessing the shared resources such as the off-chip memory. These processor cores can starve other processor cores that have less burst data transactions while accessing the same shared resources. The starving issue of other processor cores leads to degrade the entire system performance of the SoC. However, the arbiter architecture in the SoC design plays the best solution to manage different processor core requests and granting one of them to access the shared resources according to different scheduling algorithms. In this paper, we have designed AXI interconnect, which includes arbiter architecture to connect four processor cores represented by the AXI masters and the off-chip memory represented by the salve. Each processor core (AXI Master) uses the AXI4 interface protocol to improve the system performance and the arbiter based on the static fixed-priority algorithm to improve the average waiting time for all the processor cores. The SoC design architecture is modeled in System Verilog HDL; simulation and synthesis are done by using the Vivado tool and FPGA ZYNQ-7 ZC702 Evaluation Board (xc7z020clg484-1).